2016
DOI: 10.1186/s40064-016-3665-4
|View full text |Cite
|
Sign up to set email alerts
|

Thailand’s universal coverage scheme and its impact on health-seeking behavior

Abstract: BackgroundThailand’s Universal Coverage Scheme (UCS) has improved healthcare access and utilization since its initial introduction in 2002. However, a substantial proportion of beneficiaries has utilized care outside the UCS boundaries. Because low utilization may be an indication of a policy gap between people’s health needs and the services available to them, we investigated the patterns of health-seeking behavior and their social/contextual determinants among UCS beneficiaries in the year 2013.ResultsThe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 13 publications
3
69
0
Order By: Relevance
“…At Ramathibodi Hospital, the majority of devices that increased were PPM. The marked increased rate of implantation might be the result of the start of Thailand's Universal Coverage Scheme in 2002, which covered approximately 75% of the entire Thai population, making more patients able to access the appropriate treatment . Our study demonstrated that the annual incidence of CIED infection at Ramathibodi Hospital was stable at approximately 0.9% despite a continuous rise in CIED implantation.…”
Section: Discussionmentioning
confidence: 63%
“…At Ramathibodi Hospital, the majority of devices that increased were PPM. The marked increased rate of implantation might be the result of the start of Thailand's Universal Coverage Scheme in 2002, which covered approximately 75% of the entire Thai population, making more patients able to access the appropriate treatment . Our study demonstrated that the annual incidence of CIED infection at Ramathibodi Hospital was stable at approximately 0.9% despite a continuous rise in CIED implantation.…”
Section: Discussionmentioning
confidence: 63%
“…To understand the economic burden that AD poses in Asia, it is important to first be aware of the varied medical reimbursement systems used in different Asian countries. For the most part, many Asian countries, including South Korea, Thailand and Taiwan, pay for health care primarily through government‐funded or subsidized basic universal health care, although many also include a smaller private insurance sector (Table ) . Others may have a mixture of public and private health‐care systems, such as in India or Malaysia.…”
Section: Economic Burdenmentioning
confidence: 99%
“…For the most part, many Asian countries, including South Korea, Thailand and Taiwan, pay for health care primarily through governmentfunded or subsidized basic universal health care, although many also include a smaller private insurance sector (Table 1). [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] Others may have a mixture of public and private health-care systems, such as in India or Malaysia. There are some notable nuances among Asian countries when it comes to paying for AD treatment.…”
Section: Economic Burdenmentioning
confidence: 99%
“…In Thailand, the cost of bacterial culture was covered by the national health-care system even before the implementation of Thailand’s Universal Healthcare Coverage Scheme in 2002. 10 In Indonesia in 2015, the cost of bacterial culture was covered by the government only if bacterial culture was included within the package of fee for service for the final diagnosis. 11 Thailand also has a strong infectious disease society and the importance of blood culture prior to the initiation of parenteral antimicrobials has been supported widely by the society, which probably contributes to the increased utilization of clinical microbiology laboratories in Thailand compared with that observed in Indonesia.…”
mentioning
confidence: 99%